(untitled) (Research, Society and Development, 2022)
Objective: To present an integrative review of the literature on the sexuality of the elderly and the role of nurses in the prevention of Sexually Transmitted Infections (STIs) in the elderly. Methods: This is an Integrative Literature Review (RIL). It took place through searches for information on the theme in databases such as: Scielo, Virtual Health Library (VHL), Latindex and Google Scholar. The inclusion criteria were full articles published in Portuguese, English and Spanish; full articles that addressed the exposed theme and published and indexed articles from 2014 to 2020. 135 articles were found, of which 14 were selected. Thesis articles, dissertation and letter from the editor were excluded. Result: As a result of the flowchart 5 classes. Equating the percentages of words in the corpus, class 1 matches 17.2% of words in the corpus, class 2 corresponds to 16.8%, class 3 corresponds to 18.3%, class 4 corresponds to 23.1% and class 5 corresponds to 24.6%. Conclusion: The construction of the RIL provided enriching knowledge, making it possible to observe and understand the STIs and increase the number of cases reflecting the gaps that exist in relation to this theme and the expansion of new knowledge for nursing professionals and academics.